"(S)he Conquers Who Endures": Theodora DeWolf Colt and the Birth of a New Cultural Elite. Issue 1 (2nd January 2017) - Tucker, Kenneth H.; Tucker, Barbara M.
ABSTRACT: This essay explores the intersection of gender and class in the making of the new "high brow" culture of the late nineteenth century, represented by the matriarch of Bristol, Rhode Island, Theodora Goujaud DeWolf Colt. Through her poetry and salons, Theodora, like other wealthy women of the time, helped fashion a new bourgeois culture, which, though centered in New York and Boston, radiated outward to the smaller cities of the U.S., such as Bristol. Although the gendered norms and practices of the time excluded her from participation in much of public life, Theodora represented a new model of autonomy for upper-class women, for she was unmarried, not dependent on a man, and an independent intellectual. Her work also demonstrated the gendered tensions inherent in the formation of this new culture, as she developed a distinctive literary perspective that subtly criticized the paternalism and bourgeois values of that era.